2021
DOI: 10.1038/s41598-021-85312-4
|View full text |Cite
|
Sign up to set email alerts
|

RAGE ligands stimulate angiotensin II type I receptor (AT1) via RAGE/AT1 complex on the cell membrane

Abstract: The receptor for advanced glycation end-products (RAGE) and the G protein-coupled angiotensin II (AngII) type I receptor (AT1) play a central role in cardiovascular diseases. It was recently reported that RAGE modifies AngII-mediated AT1 activation via the membrane oligomeric complex of the two receptors. In this study, we investigated the presence of the different directional crosstalk in this phenomenon, that is, the RAGE/AT1 complex plays a role in the signal transduction pathway of RAGE ligands. We generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…For instance, dietary sodium restriction promoted important adverse effects on systemic glycolipid metabolism and vascular injuries, many of which were inhibited by AET, however, we did not examine intracellular signaling pathways that modulate the demonstrated biological responses presented in our study. Previous studies showed a complex crosstalk between the RAAS and the AGE/RAGE axis [53][54][55][56], however, such signaling pathways were not explored and were just inferred in this experimental model as a theoretical basis to support the results from the present study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For instance, dietary sodium restriction promoted important adverse effects on systemic glycolipid metabolism and vascular injuries, many of which were inhibited by AET, however, we did not examine intracellular signaling pathways that modulate the demonstrated biological responses presented in our study. Previous studies showed a complex crosstalk between the RAAS and the AGE/RAGE axis [53][54][55][56], however, such signaling pathways were not explored and were just inferred in this experimental model as a theoretical basis to support the results from the present study.…”
Section: Discussionsupporting
confidence: 55%
“…AT1 receptor signaling triggers oxidative stress, inflammatory response, and lipid peroxidation [ 51 , 52 ], which favor the CML generation and RAGE expression in the arterial wall in a positive-feedback loop, as previously demonstrated in sodium restriction [ 8 ]. It has been reported that the interplay between the RAAS signaling pathways and the AGE/RAGE axis sets up an effective positive-feedback loop that promotes arterial dysfunction and injury [ 53 , 54 , 55 ]. In this regard, chronic infusion of ANG II in Sprague–Dawley rats increased plasma and renal concentration of AGE, effects that were antagonized by pyridoxamine, an inhibitor of AGE generation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated whether ACE inhibitors (captopril, lisinopril) or AT 1 R antagonists (telmisartan, olmesartan) regulate ACE2 mRNA expression. For that purpose, Caco-2 cells were incubated with increasing drug concentrations for 24 h, 48 h, and 72 h. The selected concentrations are in the range of c max plasma levels in humans [ 17 , 18 , 19 , 20 , 21 , 22 ], high enough to inhibit ACE [ 23 ] or block AT 1 R receptor [ 24 ] and typically used for in vitro experiments [ 25 , 26 , 27 ]. However, there was no concentration-dependent alteration of the ACE2 mRNA expression ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, both AGE-induced MAPK activity and epithelial mesenchymal transition (EMT) in rat NRK-52E cells are blocked by treatment with AT1R blockers (e.g., olemesartan, irbesartan, losartan) ( 64 ). In NRK-52E epithelial cells, DIAPH1 is a necessary factor in the production of TGF-β1, type I collagen, profilin1, and α-SMA.…”
Section: Epithelial Cellsmentioning
confidence: 99%